Tim-3 Expression in Cervical Cancer Promotes Tumor Metastasis - Cao, Yang (Public Library of Science, 2013)
BACKGROUND: T cell immunoglobulin mucin-3 (Tim-3) has been identified as a negative regulator of anti-tumor immunity. Recent studies highlight the important role of Tim-3 in the CD8(+) T cell exhaustion that takes place in both human and animal cancer models. However, the nature of Tim-3 expression in the tumor cell and the mechanism by which it inhibits anti-tumor immunity are unclear. This present study aims to determine Tim-3 is expressed in cervical cancer cells and to evaluate the role of Tim-3 in cervical cancer progression. METHODOLOGY: A total of 85 cervical tissue specimens including 43 human cervical cancer, 22 cervical intraepithelial neoplasia (CIN) and 20 chronic cervicitis were involved. Tim-3 expression in tumor cells was detected and was found to correlate with clinicopathological parameters. Meanwhile, expression of Tim-3 was assessed by RT-PCR, Western Blot and confocal microscopy in cervical cancer cell lines, HeLa and SiHa. The migration and invasion potential of Hela cells was evaluated after inhibiting Tim-3 expression by ADV-antisense Tim-3. CONCLUSIONS: We found that Tim-3 was expressed at a higher level in the clinical cervical cancer cells compared to the CIN and chronic cervicitis controls. We supported this finding by confirming the presence of Tim-3 mRNA and protein in the cervical cell lines. Tim-3 expression in tumor cells correlated with clinicopathological parameters. Patients with high expression of Tim-3 had a significant metastatic potential, advanced cancer grades and shorter overall survival than those with lower expression. Multivariate analysis showed that Tim-3 expression was an independent factor for predicting the prognosis of cervical cancer. Significantly, down-regulating the expression of Tim-3 protein inhibited migration and invasion of Hela cells. Our study suggests that the expression of Tim-3 in tumor cells may be an independent prognostic factor for patients with cervical cancer. Moreover, Tim-3 expression may promote metastatic potential in cervical cancers.